2023
DOI: 10.1101/2023.03.15.532597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primate Cerebellar Scaling in Connection to the Cerebrum: A 34-Species Phylogenetic Comparative Analysis

Abstract: The cerebellum has increasingly been recognized for its role in diverse functional processes. The reciprocal cerebello-cerebral system may scaffold both brain size increase and advanced associative abilities, evolving highly coordinately in primates. In parallel, functional cerebello-cerebral modules have undergone reorganization and cerebellar lobules crura I-II (the ansiform area across mammals) have been reported to be specifically expanded in humans. Here we manually segmented 63 cerebella (34 primate spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 156 publications
(411 reference statements)
1
3
0
Order By: Relevance
“…Our results showed two very different groups of phenotypes: those like brain size, that changed over several orders of magnitude, and those like folial width which were much more conserved. We confirm the strong allometry between the size of the cerebellum and the cerebrum across mammals ( Barton and Harvey, 2000 ; Barton, 2002 ; Whiting and Barton, 2003 ; Herculano-Houzel, 2010 ; Barton, 2012 ; Smaers et al, 2018 ; Ashwell, 2020 ; Magielse et al, 2023 ) and show similarly strong relationships for the width of cerebellar folds and the thickness of the molecular layer, although with a much narrower range of variation. This deeply conserved pattern suggests the presence of a common mechanism underlying the development of the cerebellum and cerebellar folding across mammals.…”
Section: Introductionsupporting
confidence: 78%
“…Our results showed two very different groups of phenotypes: those like brain size, that changed over several orders of magnitude, and those like folial width which were much more conserved. We confirm the strong allometry between the size of the cerebellum and the cerebrum across mammals ( Barton and Harvey, 2000 ; Barton, 2002 ; Whiting and Barton, 2003 ; Herculano-Houzel, 2010 ; Barton, 2012 ; Smaers et al, 2018 ; Ashwell, 2020 ; Magielse et al, 2023 ) and show similarly strong relationships for the width of cerebellar folds and the thickness of the molecular layer, although with a much narrower range of variation. This deeply conserved pattern suggests the presence of a common mechanism underlying the development of the cerebellum and cerebellar folding across mammals.…”
Section: Introductionsupporting
confidence: 78%
“…However, it should be noted that only up to 12 primate species were investigated in these studies with only 2 prosimian species involved. A recent study ( Magielse et al, 2023 – preprint) investigated cerebellar volumes in 34 primate species including 9 prosimian species (mostly Lemuriformes ). Here it was found that the volume of cerebellum relative to the rest of the brain varies across primates with the highest ratios displayed by prosimian species but also by human and non-human apes.…”
Section: Discussionmentioning
confidence: 99%
“…Several atlases of the human brain stem that included the RN have been published recently based on histological sections of single brain specimen (Coulombe et al, 2021), post-mortem MRI of a single brain specimen (Adil et al, 2021;Lechanoine et al, 2021) as well as large in vivo MRI data set creating probabilistic maps (Pauli et al, 2018). An atlas based on the combination of histological sections showing the cyto-and chemoarchitecture and MRI has been recently introduced by Agostinelli et al (2023). Unfortunately, the level of midbrain containing RN has not been included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar functions have been emphasized in light of Box 1 | Summary of the kinds of data obtainable from the fossil record, unresolved questions about the origin of the human mind, and emerging directions that incorporate interdisciplinary research tools and innovative pipelines, making it possible to now answer those questions. Illustrating this is the natural partial endocast STS 60, from the collection at the Ditsong National Museum of Natural History, Pretoria, South Africa (photo on left) which preserves brain features that can then be compared to extant species (graphic on right; adapted from Heuer et al 26 ) recent findings supporting structural, size, and molecular changes in the cerebellum in humans [198][199][200][201][202] .…”
Section: Emerging Directionsmentioning
confidence: 99%